On a necessary condition for belonging of a function to periodic generalized Nikol’sky-Besov-Morrey space in terms of strong summability of Fourier series - Baituyakova, Zh.Zh. (Вестник Карагандинского университета, 2016)
This paper is dedicated to the investigation of strong summability in the generalized Morrey spaces. First, we study boundedness of the Hardy-Littlewood maximal function on generalized Morrey spaces. We find a necessary condition for belonging of a function to the periodic generalized Nikol’skij-Besov-Morrey spaces.
Keywords: Morrey space; maximal function; Fourier transform; Nikol’skij-Besov-Morrey space